THE STRATEGIES FOR TEACHING EARLY CHILDHOOD ENGLISH EDUCATION - Paramitasari, Ayu (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2022)
Early childhood education basically aims to provide stimulation in all aspects of child development including physical, intellectual, social, emotional and language development to develop optimally. To provide a good education for early childhood we must understand their characteristics and needs according to the level of child development. So we have to provide activities that suit the needs of students and deliver them in the right way. In accordance with the world of early childhood, children learn through play (learning through play) and playing is a learning process for them (playing is learning). Therefore we have to give them activities in a way that fits their world: play.